Fault Switching and Mode Analysis of Differential Mechanism Under Friction Load - Liu Ting; Zhao Guoping; Yan Haiyuan; Cui Peijuan; Sun Xuyao (Jixie chuandong)
In order to analyze fault-switching of two input differential mechanism under conditions of acceleration and deceleration,the rigid-body dynamics formulae of planet differential mechanism are deduced theoretically when two inputs worked together and only one input worked. The laws of the formulae are summarized.Fault switching procedures and mode analyses are analyzed in conditions of one channel（ master-alternate） and two channels（ master-master）. The analysis got the conclusion as follows. When there is only friction load at the output of the differential mechanism,it is deduced that direction of friction load is always opposite to the direction of velocity. This characteristic that friction load is resisting force but not dynamic force whether or not the switchover path is switched over. The characteristic contributes to deceleration braking of faulty channel. Four fault-switching schemes are analyzed. The first scheme is always single channel module. The accelerating capacity of one way is better than two ways. The switching procedure of the first scheme is simple. The switching time of the first scheme is short. Thus the first scheme is recommended.